Effect of inoculum origin and substrate-inoculum ratio to enhance the anaerobic digestion of organic fraction municipal solid waste (OFMSW). (1st June 2022) - Demichelis, F.; Tommasi, T.; Deorsola, F.A.; Marchisio, D.; Fino, D.
Abstract: This study evaluated the key role of inoculum in mesophilic anaerobic digestion (AD) of Organic Fraction of Municipal Solid Waste. The effect of two different inocula, the mesophilic digestate of wastewater activated sludge (WAS) and the mesophilic digestate of cow-agriculture sludge (CAS), at three different substrate: inoculum ratios (1:2, 1:1 and 2:1) at three different incubation times (0, 5 and 10 d) were studied in batch feeding reactor for a total of 18 AD configurations. The AD configurations were study through specific biogas and methane productions, first order disintegration kinetics, Gompertz modified study and energy sustainable index. A multi criteria decision aid outranked the 18 AD configurations tested. The study proved that the AD performed with inoculum CAS incubated for 10 d at 2:1 substrate inoculum ratio reached the highest biogas yield and methene content equal to 997.81 NL/kgVS and 70.00% v/v. Highlights: Optimisation of anaerobic digestion (AD) to increase methane content up to 70 %v/v. AD performed with inoculum incubated 5–10 d can work at higher substrate: inoculum mass ratio. AD performed with inoculum incubated for 5 and 10 d reaches ESI higher than 1. For inocula incubated for 5–10 d the kd is higher (0.49 d −1 ). The lag phase is reduced from 4 to 0 d with incubated inoculum.